2008
DOI: 10.1002/ijc.23518
|View full text |Cite
|
Sign up to set email alerts
|

How basal are triple‐negative breast cancers?

Abstract: The basal molecular subtype of breast cancer (BC) is defined by the mRNA expression pattern of an intrinsic 500-gene set. It is the most homogeneous subtype in transcriptional terms, and one of the most aggressive in prognostic terms. Clinical trials testing new systemic therapeutic strategies have been launched in basal BCs. Although no proof of evidence has yet been reported, basal tumors are currently assimilated to and selected as triple-negative (TN) BCs in these trials because of their frequent immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
305
0
14

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(333 citation statements)
references
References 33 publications
14
305
0
14
Order By: Relevance
“…Basal like cancers cell of origin is thought to be from the basal/ myoepithelial cells and they express high molecular weight basal cytokeratins (CK 5/6, CK 14, CK 17), vimentin, p-cadherin, EGFR, etc., in contrast to luminal cancers which originate from a differentiated luminal precursor cell. Birnbaum et al performed a study by using 500 gene set to 172 cases of TNBC; in which he found 71.5% of patients who were triple negative expressed markers for basal carcinoma and 23.1% patients who were triple negative failed to express these markers for basal like cancer [8]. Also TNBC, are commonly associated with high nuclear mitotic grade, larger tumour size, more aggressive expression profile with low Bcl-2 expression and high expression of p53, Rb gene mutations and increased Ki67 expression [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal like cancers cell of origin is thought to be from the basal/ myoepithelial cells and they express high molecular weight basal cytokeratins (CK 5/6, CK 14, CK 17), vimentin, p-cadherin, EGFR, etc., in contrast to luminal cancers which originate from a differentiated luminal precursor cell. Birnbaum et al performed a study by using 500 gene set to 172 cases of TNBC; in which he found 71.5% of patients who were triple negative expressed markers for basal carcinoma and 23.1% patients who were triple negative failed to express these markers for basal like cancer [8]. Also TNBC, are commonly associated with high nuclear mitotic grade, larger tumour size, more aggressive expression profile with low Bcl-2 expression and high expression of p53, Rb gene mutations and increased Ki67 expression [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, they are not synonymous? Approximately 75% of basal like cancers are triple negative but 25% of them may express Her2 or hormone receptors and similarly around 70-75% of tripe negative cancers are basal like cancers [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,15,69 Taken together, these results are in accord with the concept that the triple-negative phenotype is not an ideal surrogate marker for basal-like breast cancers. 60,70,81 Relationship between basal-like breast cancer and BRCA1 germ-line mutations There is increasing evidence to suggest a link between BRCA1 pathway and basal-like breast cancers. 82,83 The majority of tumors arising in BRCA1 germ-line mutation carriers, in particular those diagnosed before 50 years of age, have morphological features similar to those described in basal-like cancers 84,85 and show a basal-like phenotype as defined by immunohistochemistry 86,87 or expression arrays.…”
Section: S Badve Et Almentioning
confidence: 99%
“…10 Genomic studies such as the PAM50 gene expression assay have demonstrated that breast cancers can be classified into at least five intrinsic subtypes (luminal A, luminal B, HER2-enriched, basal-like and normal breast-like). 11 Triple-negative breast cancers overlap with the molecular entity of 'basallike' breast cancers, 12 but these are not the same entity and equating them is misleading. [13][14][15] Many current studies make use of microarray-based expression profiling to define basal-like breast cancers; however, continuous efforts are being made to define these lesions with standard pathological techniques, for example, using immunohistochemical markers as surrogates.…”
mentioning
confidence: 99%